Joint Adoption of Microcomputer Technologies: An Analysis of Farmers' Decisions - Huffman, Wallace E.; Mercier, Stephanie (The Review of Economics and Statistics, 1991)
This study presents an econometric examination of the joint decisions of farmers on the adoption of a microcomputer and (or) purchased computers services. The characteristics of a farmer–schooling, age, off-farm work–are shown to be important variables for explaining the odds of adopting purchased computers services only, a microcomputer only, and both computer technologies. Adoption of computer technologies seems to occur in farming operations where they can be expected to greatly enhance the efficiency. Copyright 1991 by MIT Press.